PENYERAPAN TENAGA KERJA DI JAWA TIMUR: ANALISIS PERTUMBUHAN EKONOMI, UPAH MINIMUM, JUMLAH UNIT INDUSTRI, DAN KONSUMSI TEMBAKAU - Amin Prawiro Madhani; Masruri Muchtar; Pardomuan Robinson Sihombing (LPPM Universitas Bina Bangsa, 2024)
Tobacco Plant Production in Indonesia is very massive. East Java is Indonesia's largest tobacco producer. In addition, the tobacco processing industry in East Java contributes one-third of East Java's GDP. This study aims to determine the effect of tobacco consumption, GRDP, district/city minimum wage, processing business units on the absorption of processing industry workers in East Java in 2019-2022. The research method uses a quantitative approach with statistical analysis of regression of fixed effect model (FEM) panel data. The results of the regression analysis of panel data show that an increase in GDP, MSEs, and processing industry units will have a positive effect on employment, while an increase in tobacco consumption will reduce employment. This has implications for the need for appropriate MSE policies, economic growth policies that are in accordance with regional characteristics, the development of new processing industries, and appropriate management of labor-intensive tobacco processing industries